The caatinga in science and geography books in schools in the desertification nucleus of Irauçuba, Ceará - Castro Filho, Pedro Julio de; Albuquerque, Francisco Nataniel Batista de (Revista Ensino de Geografia (Recife), 2022)
The Caatinga is an important theme to be taught in Primary Education, especially in the teaching of Science and Geography. Textbooks are considered in many schools as the main resource used in the classroom, complementing the pedagogical practice and assisting the teacher in the uses and applications of the proposed contents in their practice. In this sense, the textbooks play an important role in the approach of the contents necessary for the teaching-learning process, which includes the teaching of the Caatinga. This study aimed at analysing the contents on Caatinga in the 7th grade Science and Geography textbooks of the municipal schools of Irauçuba and Sobral, both located in the northwest of the State of Ceará. The research, qualitative in nature, resorts to the method of documentary analysis, using the teaching materials of 06 schools. As results, although some analysis criteria have been considered satisfactory in some books, it was found that the contents relating to Caatinga in the 7th grade Science and Geography books, in general, fail to bring a consistent and in-depth approach, prevailing the idea that these contents are placed in the background and decontextualized from the reality and coexistence of students.